ОСОБЕННОСТИ ПСИХОРЕЧЕВОГО РАЗВИТИЯ ДЕТЕЙ, ЗАЧАТЫХ С ПОМОЩЬЮ ЭКО И РОДИВШИХСЯ В МНОГОПЛОДНОЙ БЕРЕМЕННОСТИ - Зверева, Наталья Владимировна; Суркова, Каролина Леонидовна; Сергиенко, Алексей Анатольевич; Строгова, Светлана Евгеньевна; Зверева, Мария Вячеславовна (FORCIPE, 2022)